Comparative Study of Cow Urine Extract and Hydroalcoholic Extract for In-Vitro Anti-Inflammatory Potential of Nycanthesarbos-Tritis Leaves - Yogesh Choudhary,; Dr. R.Y. Patil,; Sayam Bohra,; Abhijeet Choudhari, (International Journal of Scientific Research in Science and Technology, 2024)
Nyctanthesarbor-tristis, commonly referred to as "Night jasmine," is widely used in Ayurvedic medicine. to evaluate Nyctanthesarbor-tristis ethanolic bark extract's potential for anti-inflammatory properties. The results of the preliminary phytochemical analysis showed the presence of tannin, glycosides, alkaloids, and flavonoids. distinct amounts: 50, 100, 200, 400, and 800 µg/ml. Nyctanthesarbor-tristis was used to consider the denaturation of albumin during in-vitro anti inflammatory exercises. The results suggested that the presence of the flavonoid quercetin in Nyctanthesarbor-tristis was logically responsible for its anti-inflammatory activity. Therefore, it can be used as a possible source ofanti-inflammatory agent.
Keywords: Nyctanthes arbor-tristis; anti-inflammatory